Thermal Tolerances of Three Tramp Ant Species (Hymenoptera: Formicidae) - Solis, Daniel Russ [UNESP]; Bueno, Odair Correa [UNESP] (California State University, 2012)
Tramp ant species present a set of adaptations to their urban habitats, and there is a paucity of knowledge about how they interact with abiotic factors, like temperature. Temperature is well known to interfere with insect activity. The present study evaluated the temperature tolerance of three important tramp ant species: Monomorium floricola (Jerdon), Monomorium pharaonis (Linnaeus) and Tetramorium bicarinatum (Nylander). Tested temperatures were 0, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 25, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48 and 50 degrees C. Ten repetitions with 20 workers each were done with each temperature and analyzed species. The number of dead workers was recorded every hour over a total of 8 hours. All procedures were done using thermal incubators at relative humidity within 50-95%. Workers of M. pharaonis proved more tolerant to high temperatures (30-50 degrees C) than workers of M. floricola and T bicarinatum. The higher the temperatures tested, greater was the recorded ant mortality, with temperature 50 degrees C being fatal to all species after 1h of exposition. The least tolerant species to temperatures below 20 degrees C was T bicarinatum. Low temperatures tested were not fatal to any of the tested species.
Keywords: Myrmicinae; Monomorium floricola; Monomorium pharaonis; Tetramorium bicarinatum